Cluster sets vs. traditional sets: Levelling out the playing field using a power-based threshold - Tufano, James J; Halaj, Matej; Kampmiller, Tomas; Novosad, Adrian; Buzgo, Gabriel (PloS one, 2018)
Cluster sets allow for velocity and power output maintenance, but the literature routinely uses highly fatiguing traditional set protocols. Although such studies have merit, others suggest fatigue should be avoided when training to improve power output, making those cluster set studies less practical. Therefore, the purpose of this study was to compare these set structures when truncating sets using a power-based threshold. Nine males (23.4 ± 0.6 yr) with various sport backgrounds performed 6 sets of back squats with individualized loads that elicited the greatest mean power (MPmax) output (112.7 ± 12.1% of body mass). Each set during the traditional set (TS) protocol included as many repetitions as possible until two consecutive repetitions dropped below 90% MPmax, which was followed by 120 s inter-set rest. The design was identical for cluster sets (CS) but with an additional 20 s intra-set rest after every 2 repetitions. The number of repetitions performed, mean velocity, and mean power output, were analyzed using 2(protocol)*6(set) repeated measures ANOVA. The number of repetitions during CS (51.8 ± 14.4) was greater than TS (31.9 ± 3.7) (p = 0.001), but the average velocity (CS = 0.711 ± 0.069, TS = 0.716 ± 0.081 m·s-1; p = 0.732) and power output (CS = 630.3 ± 59.8, TS = 636.0 ± 84.3 W; p = 0.629) of those repetitions were similar. These data indicate that CS are a viable option for increasing training volume during contemporary training where sets are ended when repetitions drop below velocity or power thresholds.
Keywords: Weight Lifting; mužské pohlaví; Young Adult; sportovci; Humans; mladý dospělý; vzpírání; Athletes; lidé; Male